ANALISIS EFEKTIVITAS PENYALURAN DANA ZAKAT, INFAK DAN SEDEKAH PADA YAYASAN RUMAH ZAKAT - Ahmad Yudhira (VALUE, 2020)
This study aims to determine the effectiveness of the distribution of funds (use of assets) at the Rumah Zakat Foundation by using the allocation to collection ratio (ACR). This research uses a combination of qualitative and quantitative methods. The research data was obtained by taking the publication of the financial statements of the zakat house foundation in 2018. Based on the results of the study it was concluded that the distribution of funds (use of assets) at the Rumah Zakat Foundation using the allocation to collection ratio (ACR) was very effective. Gross Allocation to Collection Ratio of 0.892 (89.17%); Gross allocation to non-amil collection ratio of 0.874 (87.40%); Net Allocation to collection Ratio of 0.997 (99.71%); net Allocation to non-amil collection for 0.997 (99.66%).